Phreatophytes in southwest Kansas used as a tool for predicting hydrologic properties - Ahring, Trevor S. (Kansas State University, 2009)
The Ogallala Aquifer is a supply of water for several municipalities in western Kansas, as well as an irrigation source for local farmers. Since the 1950’s, when the aquifer started to be pumped for irrigation, the region has seen steady declines of the groundwater table. These declines have reduced stream flow in the Arkansas and Cimarrron Rivers, and caused a redistribution of riparian phreatophytes. This thesis studies this redistribution of phreatophytes, and develops statistical relationships relating a phreatophyte’s location to depth to groundwater, increase in depth to groundwater, distance from a stream or river, and hydrologic soil group. Remote sensing was used to determine tree locations on predevelopment and post-development aerial photography. These locations were mapped using ArcGIS, and ArcAEM was used to model groundwater flow in six riparian regions taking root uptake into account. It was found that once the depth to groundwater becomes greater than about 3 m, tree population will decrease as depth to water increases. Trees were located within 700 m of the river. Areas with a dense tree population (>10% tree cover) occurred where the average depth to water ranged from 0.24-1.4 m. Areas with moderate tree density (5-10% tree cover) corresponded to an average depth to water ranging from 2.1-19 m. Areas with a low tree density (<5% tree cover) corresponded to an average depth to water ranging from 11-28 m. It was found that phreatophytes have a high likelihood of growing on hydrologic soil group A and a low likelihood of growing on hydrologic soil group B. The number of trees located on hydrologic soil group D was what would be statistically expected if tree location were independent of soil type. It was also found that tree locations could be used as an indicator of good hydraulic connectivity between surface water and groundwater. This information can be used to help guide future installation of monitoring networks and expand research projects from central Kansas to western Kansas.
Keywords: Phreatophyte; Water Balance; Remote Sensing; ArcGIS; Arkansas River; Cimarron River; Engineering, Civil (0543); Engineering, Environmental (0775); Remote Sensing (0799)